Physical fitness reference standards in French youth: The BOUGE program - Vanhelst, J.; Julien, J. L.; Beghin, L.; Drumez, E.; Fardy, P. S.; Chapelot, D.; Mikulovic, J.; Ulmer, Z. (The Journal of Strength and Conditioning Research, 2017)
The aim of this study was to establish sex- and age-specific physical fitness percentiles in French youth. A sample of 11,186 children and adolescents (5,546 boys and 5,640 girls), aged between 10 and 15 years, was assessed in the French national BOUGE study. Participants were tested for their cardiorespiratory fitness, muscular endurance, speed, flexibility, and agility using the following tests: 20-m shuttle run tests, curl-ups test, 50-m sprint test, back-saver sit and reach test, and 10 × 5-m shuttle run test. Percentile values were estimated for French youth as a function of age stratified by sex using the generalized additive model for location, scale, and shape (GAMLSS). In general, physical fitness was better in boys than in girls, except for the back-saver sit and reach test, in which girls performed better. Except for the back-saver sit and reach test and 10 × 5-m shuttle run test, physical fitness performance was significantly associated with age. Sex- and age-specific normative values for physical fitness tests in French youth expressed as percentiles from the fifth to the 95th are provided. Reference values provide normative data for French youth. The data are useful in identifying special needs for appropriate intervention programs.